Balancing Acts : Youth Culture in the Global City - Warikoo, Natasha Kumar, 1973- (Book collections on Project MUSE., 2011)
In this timely examination of children of immigrants in New York and London, Natasha Kumar Warikoo asks, Is there a link between rap/hip-hop-influenced youth culture and motivation to succeed in school? Warikoo challenges teachers, administrators, and parents to look beneath the outward manifestations of youth culture -- the clothing, music, and tough talk -- to better understand the internal struggle faced by many minority students as they try to fit in with peers while working to lay the groundwork for successful lives. Using ethnographic, survey, and interview data in two racially diverse, low-achieving high schools, Warikoo analyzes seemingly oppositional styles, tastes in music, and school behaviors and finds that most teens try to find a balance between success with peers and success in school.